Developmental Processes of Cooperative Interorganizational Relationships - Ring, Peter Smith; Ven, Andrew H. Van de (Academy of Management Review, 1994)
This article examines the developmental process of cooperative interorganizational relationships (IORs) that entail transaction-specific investments in deals that cannot be fully specified or controlled by the parties in advance of their execution. A process framework is introduced that focuses on formal, legal, and informal social-psychological processes by which organizational parties jointly negotiate, commit to. and execute their relationship in ways that achieve efficient and equitable outcomes and internal solutions to conflicts when they arise. The framework is elaborated with a set of propositions that explain how and why cooperative IORs emerge, evolve, and dissolve. The propositions have academic implications for enriching interorganizational relationships, transaction cost economics, agency theories, and practical implications for managing the relationship journey.